Parasites and Microbes On the Bodies of Mosquitoes: A Systematic Review Based on the Tafsir of Surat Al-Baqarah, 2:26 and Signs in Modern Medicine - Kitota, Abdillah Mussa (Journal of Quranic Sciences and Research, 2023)
This study has adopted a qualitative systematic review design to analyze the reason behind the revelation of Qur’an, 2:26 and its implications according to the signs in modern medicine. The relevant tafsir of the Qur’anic verses were collected from famous tafsir of the Qur’an. Data concerning modern medicine were collected from the published articles screened from MEDLINE and PUBMED databases. Data were then analyzed by Thematic analysis to show what Allah (S.W.T) has shown the medical experts with regard to what He has revealed in this verse. The results show that the phrase ????? ????????? used in the phrase ????? ??????? ??? ??????????? ??? ???????? ??????? ???? ????????? of this verse exposes that Allah (S.W.T) has dispersed small creatures [such as parasites and microbes] ‘on top’ of the mosquitoes’ bodies. This study may provide us with a glimpse of the wonders of the Qur’an and the Majesty of Allah (S.W.T).